High-Power and Ultralong-Life Aqueous Zinc-Ion Hybrid Capacitors Based on Pseudocapacitive Charge Storage - Dong, Liubing; Yang, Wang; Yang, Wu; Wang, Chengyin; Li, Yang; Xu, Chengjun; Wan, Shuwei; He, Fengrong; Kang, Feiyu; Wang, Guoxiu (Nano-Micro Letters, 2019)
Rechargeable aqueous zinc-ion hybrid capacitors and zinc-ion batteries are promising safe energy storage systems. In this study, amorphous RuO2·H2O for the first time was employed to achieve fast and ultralong-life Zn2+ storage based on a pseudocapacitive storage mechanism. In the RuO2·H2O||Zn zinc-ion hybrid capacitors with Zn(CF3SO3)2 aqueous electrolyte, the RuO2·H2O cathode can reversibly store Zn2+ in a voltage window of 0.4–1.6 V (vs. Zn/Zn2+), delivering a high discharge capacity of 122 mAh g−1. In particular, the zinc-ion hybrid capacitors can be rapidly charged/discharged within 36 s with a very high power density of 16.74 kW kg−1 and a high energy density of 82 Wh kg−1. Besides, the zinc-ion hybrid capacitors demonstrate an ultralong cycle life (over 10,000 charge/discharge cycles). The kinetic analysis elucidates that the ultrafast Zn2+ storage in the RuO2·H2O cathode originates from redox pseudocapacitive reactions. This work could greatly facilitate the development of high-power and safe electrochemical energy storage. Highlights: 1 This work starts the research of pseudocapacitive oxide materials for multivalent Zn2+ storage. 2 The constructed RuO2·H2O||Zn systems exhibit outstanding electrochemical performance, including a high discharge capacity, ultrafast charge/discharge capability, and excellent cycling stability. 3 The redox pseudocapacitive behavior of RuO2·H2O for Zn2+ storage is revealed.